Porcine Cysticercosis In Slaughtered Pigs And Factors Related To Taenia Solium Transmission Amongst Abattoir Workers In Ibadan, Nigeria (2019)
Introduction: porcine cysticercosis is under-reported particularly in Nigeria, despite the reportedly high prevalence of epilepsy and associated life-threatening health implications. This study was aimed at determining the prevalence of porcine cysticercosis and factors related to Taenia solium transmission to humans. Methods: slaughtered pigs at a major abattoir, south-western Nigeria were randomly inspected and questionnaire was administered to pig workers/consumers while the data were analysed using Stata 12.0. Results: a 4.4% (11/250) prevalence of porcine cysticercosis was obtained; the age, breed, sex and body conditions of pigs were not significant for infection (p < 0.05). Further, none (0.0%) of the respondents knew that T. solium could cause epilepsy in man and 39.5% often defaecated on neighbouring open fields and farmlands. Respondents purchasing pork from home slaughter were about four and ten times less likely to demonstrate good knowledge (OR = 0.24; 95% CI: 0.08-0.74) and practice (OR = 0.10; 95% CI: 0.05-0.22) than those purchasing from abattoir. Moreover, those lacking toilet facility were about four and five times less likely to demonstrate good knowledge (OR = 0.24; 95% CI: 0.07-0.86) and practice (OR = 0.19; 95% CI: 0.08-0.45) than those who had it. Other factors associated with practices related to T. solium transmission included age (p = 0.000), sex (p = 0.000) and duration (p = 0.003). Conclusion: the increased odds of poor knowledge and practices related to Taenia solium transmission especially among respondents purchasing home slaughter pork and lacking toilet facility provides insights into the parasite epidemiology. Above findings are important in lowering the infection prevalence in pigs and humans in this endemic area.